From Stage Carnival to Algorithmic Heroism: A Tri-Generational Analysis of Chinese Youth Values through Popular Music - Zheng, Xinzhuo (Journal of Social Science and Humanities, 2025)
This study outlines the trajectory of Chinese youth’s values from collective dependence to algorithmic collective heroism through a cross-generational textual analysis. against the backdrop of Chinese pursuit of modernization, the rise of digital capitalism and the commodification of cultural production have led three generations to construct different symbolic systems: the 1990s generation first characterized resistant collectivism as “reveling on the stage”; the 2000s generation represented resilient dialectics as “walking in the rain”; and the 2010s generation reconstructed algorithmic heroism in the face of algorithmic colonization. This evolution is not only a projection of Chinese sociopolitical changes but also an enlightening framework for understanding the formation of generational values in hypermodern society.